Unpacking the Layers of Community Engagement, Participation, and Knowledge Co-Creation when Representing the Visual Voices of LGBTQ Former Foster Youth - Moshoula Capous-Desyllas; Sarah E. Mountz; Althea Pestine-Stevens (Engaged Scholar Journal, 2019)
This article highlights the various ways in which we represented the visual voices of LGBTQ former foster youth through photovoice methodology in order to engage various stakeholders, diverse communities, and the participants themselves. We locate our research within other similar community-based, participatory projects and weave in our collective experiences. Through the juxtaposition of academic literature with the various steps of our research process, this article provides our critical reflections of our engagement process as we prepared for the research, interacted with the community, shared our findings, and incorporated social change efforts through the dissemination of  the visual data in various formal and informal spaces.